PERENCANAAN DINDING PENAHAN TANAH TIPE KANTILEVER PADA GEDUNG PERKANTORAN X DI KOTA DEPOK - Tati Noviati (Asosiasi Dosen Muda Indonesia, 2023)
An office is a building that is the center of all activities of a company. Offices can be built on a variety of land including unstable land or slopes and cliffs. Development on slopes can be easily disrupted by various things. Office buildings built on slopes require cantilever type retaining walls where cantilever type retaining walls are commonly used in soil conditions such as slopes or cliffs. The purpose of the study was to design a retaining wall and calculate the costs involved in the construction of the retaining wall. The research was conducted on an 8-story office building located on a slope or cliff by planning a cantilever type retaining wall. The cantilever type retaining wall planning method uses AutoCad and Microsoft Excel using the SNI 8460-2017 reference standard. The cantilever type retaining wall designed has dimensions of 6,00 m high and 4,20 meters wide in order to withstand the soil around the office building. The results showed that the safety factor on the slope using the Fellinius method obtained a value of 1,77 by having a retaining wall dimension area of 17,76 m2. The stability obtained in the form of shear stability of 1,51, rolling stability of 2,38 and stability of soil bearing capacity using the Terzaghi equation was found to be 5,64. The total settlement that occurred in the soil amounted to 15,56 mm. The reinforcement required on the retaining wall is D19-200, D19-166 and D19-142 on the vertical wall reinforcement while the reinforcement on the footplateis D19-142.Theresultsof the calculationofthe costbudgetplan whichincludes excavation of soil, wall formwork, reinforcement, ready mix concrete and landfill are estimated for the planning of cantilever type retaining walls amounting to Rp. 2.114.518.361.